A role for Kalirin-7 in nociceptive sensitization via activity-dependent modulation of spinal synapses - Lu, Jianning; Luo, Ceng; Bali, Kiran Kumar; Xie, Rou-Gang; Mains, Richard E.; Eipper, Betty A.; Kuner, Rohini (Nature Communications, 2015)
Synaptic plasticity is the cornerstone of processes underlying persistent nociceptive activity-induced changes in normal nociceptive sensitivity. Kalirin-7 is a multifunctional guanine-nucleotide-exchange factor (GEF) for Rho GTPases that is characterized by its localization at excitatory synapses, interactions with glutamate receptors and its ability to dynamically modulate the neuronal cytoskeleton. Here we show that spinally expressed Kalirin-7 is required for persistent nociceptive activity-dependent synaptic long-term potentiation as well as activity-dependent remodelling of synaptic spines in the spinal dorsal horn, thereby orchestrating functional and structural plasticity during the course of inflammatory pain.
Gesehen am 03.06.2020